Assessing scenic beauty of nature based-landscapes of Fraser's Hill - Othman, Jamilah (Elsevier, 2015)
This study documents results on scenic beauty preferences for thelandscapes of Fraser’s Hill. The results indicate that i) natural landscapes have influenced the tourism industry of Fraser’s Hill. ii) landscapes with good ecology and man-made attributes have significant relationship to scenic beauty iii) most tourists preferred viewing the landscapes of forest, hilly landform and architectural heritage, iv) most tourists were less preferred for the landscapes of water fall and lake. In conclusion, the attributes of forest, hilly landform and architectural heritage have significant scenic value.The insightmay suggest that scenic beauty can be an indicator to good ecology of landscapes of Fraser’s Hill.